Model for Designing Gamified Experiences Mediated by a Virtual Teaching and Learning Environment - Glenda Vera-Mora; Cecilia V. Sanz; Teresa Coma-Roselló; Sandra Baldassarri (MDPI AG, 2024)
Higher Education Institutions (HEIs) face new challenges in regard to technological development in light of necessary pedagogical and didactic innovations in educational action. This article proposes a Technological-Pedagogical Gamification Model (MGTP) that guides the design of gamified educational practices in Virtual Teaching and Learning Environments (EVEAs). The MGTP proposal is based on theoretical cores of Pedagogy and Computer Science theories, as well as works related to gamified experiences in EVEA where the social, cognitive, and teaching presences were analyzed. This work also presents an initial validation of the MGTP through expert judgment, and its results are analyzed from both a qualitative (content analysis and comments) and quantitative (using the Content Validity Coefficient method) perspective. These results reveal a high level of acceptance of the model by experts that is corroborated by reliability tests (Cronbach's alpha and split-half reliability test). The results facilitated the development of a final version of the model for its subsequent application and evaluation in university practice.